The influence of the internship semester on the beliefs of pre-service mathematics teachers: An interview study - Scherer, Simon; Rott, Benjamin (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
Teachers’ beliefs have a profound impact on the design and conceptualisation of their lessons. Those beliefs (e.g. regarding teaching methods) can go back to their times as school and university students. It has also been shown that beliefs are generally stable, and that a change is possible but requires intensive practical experience. The internship semester provides such stimulating experiences. An interview study was conducted to investigate whether and to what extent pre-service teachers’ beliefs change during the internship semester. Ten university students from all types of teaching degree Master’s programmes were interviewed individually before and after their internship semester. We analysed the interviews regarding how the students’ beliefs about the nature of mathematics as well as teaching and learning of mathematics are reflected and justified in their statements. Two contrasting developments can be identified, particularly regarding the perspective on open, problem-oriented teaching formats. Before the practical experience, some students argue in favour of understanding-oriented and problem-oriented mathematics lessons designed as a cooperative and student-centred learning process based on the learning prerequisites. Afterwards, there is a shift towards more guided, solution-oriented teaching. For other students, there is a development in which they initially rely on their experiences in tutoring situations or their educational biography. This experience is used to argue in favour of a calculus-oriented and receptive teaching in which content is presented and practice phases are supervised. The experience gained during the internship semester can lead to a shift to more open teaching formats and an argumentation from the learner’s perspective.